(untitled) (Symposium on Life and Environmental Sciences, 2026)
This study examines ethnic and cultural diversity in the Caucasus region, its historical origins, stages of development and contemporary challenges. The focus is on the relations between ethnic groups, the preservation of cultural heritage and the stability of the region. The study aims to analyze the sources and relations of ethnic conflicts from historical reality to the present day in order to identify prospects for the protection of cultural diversity and strengthening cooperation. The paper is based on both historical and contemporary scientific sources, and investigates the political, social and cultural context of the region.